Rancang Bangun Sepeda Listrik 250 Watt Dengan Pengaman NFC (Near Field Communication) - Haryanto Haryanto; Siti Sulistyawati; KuntoAji Wibisono; Deni Tri Laksono (Universitas Nurul Jadid, 2021)
In The electric bicycle is one of the many alternative fuel vehicles. This electric bicycle uses electricity as its power source. Whose electrical energy is converted into motion energy. To convert electrical energy into motion energy, an electric dynamo is needed. The electric dynamo here becomes the engine core of the electric bicycle.The purpose of this research is to design a 250 watt electric bicycle security system using NFC (Near Field Communication). This system is designed for the safety of a 250 watt electric bicycle as a contact substitute for powering a 250 watt electric bicycle with a working system to detect an NFC card (Near Field Communication) which already provided. In testing the 250 watt electric bicycle security system, the test results obtained are in accordance with what is wanted in this study, namely the 250 watt electric bicycle security system using NFC (Near Field Communication) can detect the card to read the pins that are already on the card that has been provided with output motorbikes can turn on and only the card owner can operate the 250 watt electric bicycle.